Expert Consensus for Discharge Referral Decisions Using Online Delphi - Bowles, Kathy H. (American Medical Informatics Association, 2003)
This paper describes the results of using a modified Delphi approach designed to achieve consensus from eight discharge planning experts regarding the decision to refer hospitalized older adults for post-discharge follow-up. Experts reviewed 150 cases using an online website designed to facilitate their interaction and efforts to reach agreement on the need for a referral for post-discharge care and the appropriate site for such care. In contrast to an average of eight weeks to complete just 50 cases using the traditional mail method, the first online Delphi round for 150 cases were completed in six weeks. Data provided by experts suggest that online Delphi is a time efficient and acceptable methodology for reaching group consensus. Other benefits include instant access to Delphi decision results, live knowledge of the time requirements and progress of each expert, and cost savings in postage, paper, copying, and storage of paper documents. This online Delphi methodology is highly recommended.